2016
DOI: 10.1186/s12917-016-0834-1
|View full text |Cite
|
Sign up to set email alerts
|

Feed-based vaccination regime against streptococcosis in red tilapia, Oreochromis niloticus x Oreochromis mossambicus

Abstract: BackgroundStreptococcosis is an important disease of tilapia throughout the world. In Malaysia, streptococcosis outbreak was commonly reported during the 3-month period of high water temperature between April and July. This study describes the duration of protection following single and double booster dose regimes against streptococcosis in tilapia using a feed-based vaccine containing formalin-killed Streptococcus agalactiae. A total of 510 tilapias of 120 ± 10 g were selected and divided into 3 groups. Fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 17 publications
3
46
0
2
Order By: Relevance
“…Only few descriptions of classical secondary immune responses in fish are available, but repeated injection vaccination of carp using sheep red blood cells (1‐month interval) was found to induce a secondary immune response with highly increased production of antibody producing cells (Rijkers et al., ). Other studies have indicated that repeated immunizations of tilapia with oral vaccines may lead to increased immune responses, which on the other hand are additive and not exponential (Huang et al., ; Ismail et al., ; Nur‐Nazifah, Sabri, & Siti‐Zahrah, ). With regard to rainbow trout immunized by repeated immersion vaccination, a procedure which increases and prolongs protection (Chettri et al., , ), knowledge on mechanisms behind the protection is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Only few descriptions of classical secondary immune responses in fish are available, but repeated injection vaccination of carp using sheep red blood cells (1‐month interval) was found to induce a secondary immune response with highly increased production of antibody producing cells (Rijkers et al., ). Other studies have indicated that repeated immunizations of tilapia with oral vaccines may lead to increased immune responses, which on the other hand are additive and not exponential (Huang et al., ; Ismail et al., ; Nur‐Nazifah, Sabri, & Siti‐Zahrah, ). With regard to rainbow trout immunized by repeated immersion vaccination, a procedure which increases and prolongs protection (Chettri et al., , ), knowledge on mechanisms behind the protection is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Underpinning these observations is a recent study on prime-boost vaccination against infectious salmon anemia virus where the same response pattern was observed (34). Further, the effect of repeated oral boost has recently been shown for feed-based vaccination of red tilapia ( Oreochromis niloticus x Oreochromis mossambicus ) against streptococcosis (59). In the referred studies, no attempts were made to measure IgT on mucosal surfaces, but in the study by Chen et al (60) transcript levels of IgT in the gut mucosa was measured and increased mRNA expression levels were found.…”
Section: Translating Knowledge Of Host–pathogen Interactions Into Optmentioning
confidence: 99%
“…S. agalactiae and S. iniae were recently discovered as the two most frequently detected pathogenic bacteria that trigger streptococcosis with similar clinical signs in the infected tilapia. Considering that the control strategies and zoonotic risk are different between the two species, effective methods to detect and distinguish between S. agalactiae and S. iniae are important for proper treatment of streptococcosis in aquaculture‐derived samples (Anshary, Kurniawan, Sriwulan, Ramli, & Baxa, ; Evans, Klesius, & Shoemaker, ; Ismail et al, ; Rodkhum, Kayansamruaj, & Pirarat, ).…”
mentioning
confidence: 99%
“…For example, the single PCR and ELISA assays have been applied to rapidly detect S. iniae, and the LAMP assay was applied for S. agalactiae identification (Ke, Huo, & Lu, 2014;Shelby, Shoemaker, Evans, & Klesius, 2001;Zhou, Fan, Zhu, Xie, & Li, 2011). Considering that S. agalactiae and S. iniae usually present in the same geographic area (Featherstone, 2014), duplex or multiplex PCR was developed to simultaneously and unambiguously detect S. agalactiae or S. iniae in tilapia (Itsaro, Suanyuk, & Tantikitti, 2012;Rodkhum et al, 2012).…”
mentioning
confidence: 99%